2013
DOI: 10.1051/0004-6361/201322586
|View full text |Cite
|
Sign up to set email alerts
|

GIANO-TNG spectroscopy of red supergiants in the young star cluster RSGC2

Abstract: Aims. The inner disk of the Galaxy has a number of young star clusters dominated by red supergiants that are heavily obscured by dust extinction and observable only at infrared wavelengths. These clusters are important tracers of the recent star formation and chemical enrichment history in the inner Galaxy. Methods. During the technical commissioning and as a first science verification of the GIANO spectrograph at the Telescopio Nazionale Galileo, we secured high-resolution (R 50 000) near-infrared spectra of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 28 publications
11
40
0
Order By: Relevance
“…The above spectroscopic measurements suggest either a solar or a subsolar iron abundance. This finding was reliably confirmed by Origlia et al (2013) by using high-spectral resolution (R ∼ 50 000) NIR spectra collected with GIANO at TNG. They found that the mean iron abundance of three RSGs located in the RSGC2 cluster are subsolar.…”
Section: Young Tracerssupporting
confidence: 59%
See 2 more Smart Citations
“…The above spectroscopic measurements suggest either a solar or a subsolar iron abundance. This finding was reliably confirmed by Origlia et al (2013) by using high-spectral resolution (R ∼ 50 000) NIR spectra collected with GIANO at TNG. They found that the mean iron abundance of three RSGs located in the RSGC2 cluster are subsolar.…”
Section: Young Tracerssupporting
confidence: 59%
“…There is preliminary evidence that the iron abundance in the innermost Galactic regions (nuclear bulge, Galactic bar) is more metal-poor than predicted by chemical evolution models (Minchev et al 2013). Recent spectroscopic iron abundances of young stars (red supergiants, luminous blue variables, Wolf-Rayet, O-type stars) indicate either solar or subsolar abundances (Davies et al 2009a,b;Origlia et al 2013). On the other hand, chemical evolution models suggest in the same regions iron abundances larger than [Fe/H] ∼ 0.8 (Minchev et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there are some intriguing young objects in the MW that might be related to the same phenomenon: a) the puzzling low-metallicity supergiants located near the end of the Galactic bar (Davies et al 2009a,b, see discussion in Genovali et al 2014 andOriglia et al 2013); b) the young [α/Fe]-enchanced stars reported by Cunha et al (2007) near the Galactic Centre, and; c) the unusual Cepheid BC Aql which, despite being young (Whitelock, priv. comm.)…”
Section: What Is Their Origin?mentioning
confidence: 96%
“…There are a few for the synthesis method (e.g. Önehag et al 2012;Origlia et al 2013;Rhodin 2015), and there is the large general compilation by Meléndez & Barbuy (1999). Moreover, there are line lists compiled in the NIR for the Apache Point Observatory Galactic Evolution Experiment (APOGEE) survey (see e.g.…”
Section: Introductionmentioning
confidence: 99%